(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
In the present investigation, MnxZn1-xO (x = 0.05, 0.075 and 0.1%) nanoparticles have been synthesized by simple precipitation method. Their structural, morphological and optical properties were examined by using X-ray diffraction (XRD), Field emission scanning electron microscopy (FESEM), Energy dispersive X-ray spectroscopy (EDX), High resolution transmission electron microscopy (HRTEM), Fourier transform infrared spectroscopy (FTIR), Raman spectroscopy, Differential scanning calorimetry (DSC) and UV-Visible spectroscopy. The Powder X-ray diffraction studies confirmed that the manganese doped ZnO have a single phase nature with hexagonal wurtzite structure and Mn successfully incorporated into the lattice position of Zn in ZnO lattice. The FESEM and HRTEM images are coincided with each other for aggregation of particles in nature. The elemental analysis of doped samples has been evaluated by EDX. The antibacterial activity of Mn doped ZnO nanoparticles has also been examined.